Positive Solutions for a System of Fractional Differential Equations with Two Parameters - Hongyu Li; Junting Zhang (Journal of Function Spaces)
In this paper, the existence of positive solutions in terms of different values of two parameters for a system of conformable-type fractional differential equations with the p-Laplacian operator is obtained via Guo-Krasnosel’skii fixed point theorem.